Th17/Treg-Related Transcriptional Factor Expression and Cytokine Profile in Patients With Rheumatoid Arthritis - Paradowska-Gorycka, Agnieszka; Wajda, Anna; Romanowska-Próchnicka, Katarzyna; Walczuk, Ewa; Kuca-Warnawin, Ewa; Kmiolek, Tomasz; Stypinska, Barbara; Rzeszotarska, Ewa; Majewski, Dominik; Jagodzinski, Pawel Piotr; Pawlik, Andrzej (Frontiers in Immunology, 2020)
Objectives. The aim of our study was to determine whether there is a correlation between transcription factors expression and Th17/Treg ratio, cytokine profile in the RA phenotype as well as to identify transcription factors that could be a potential biomarker for RA. Methods. The study was conducted on 45 patients with RA, 27 patients with OA and 46 healthy controls (HCs). Th17 and Treg frequency was determined by flow cytometry (15 patients with RA/ OA and 15 subjects of HC). Genes expression was estimated by qPCR, and the serum cytokine levels were determined by ELISA. Results. The percentage of Treg (CD4+CD25highCD127-) cells in RA patients was lower than in OA patients or HCs. Proportions of Th17 (CD4+CCR6+CXCR3-) cells were higher in RA and OA in comparison to HCs. STAT5 showed a very high expression in the blood of RA patients compared to healthy subjects. The expression of STAT5 and HELIOS was not detected in Th17 cells. A positive correlation between SMAD3 and STAT3 in RA patients was observed. Negative correlations between HIF-1A and SMAD2 in RA Treg cells and DAS-28 scores were observed. The range of serum of IL-17 and IL-21 were higher in RA patients than in OA patients. Concentrations of serum IL-2 and IFN-γ were higher in RA and OA patients than in healthy subjects. Based on the ROC analysis, the diagnostic potential of the combination of HIF1A, SMAD3 and STAT3, was determined at AUC 0.95 for distinguishing RA patients from HCs. For distinguishing RA patients from OA patients the diagnostic potential of the combination of SMAD2, SMAD3, SMAD4 and STAT3, was determined at AUC 0.95. Conclusion. Based on our study, we conclude that SMAD3 and STAT3 could be a potential diagnostic biomarker for RA.